Measurement of d sigma/dM and forward-backward charge asymmetry for high-mass Drell-Yan e(+)e(-) pairs from pp macro collisions at square root of s = 1.8 TeV. - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2001)
We report on a measurement of the mass dependence of the forward-backward charge asymmetry, A(FB), and production cross section d sigma/dM for e(+)e(-) pairs with mass M(ee)>40 GeV/c(2). The data sample consists of 108 pb(-1) of pp macro collisions at square root of s = 1.8 TeV taken by the Collider Detector at Fermilab during 1992-1995. The measured asymmetry and d sigma/dM are compared with the predictions of the standard model and a model with an extra Z' gauge boson.